Effects of plyometric and strength training on the physical fitness attributes of male adolescent team sports athletes: a systematic review and meta-analysis - Zhu, X.; Luo, H.; Xiang, C.; Zhao, J.; Liu, Y.; Zhang, H.; Kamalden, T. F. T. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study aims to explore the effects of plyometric training (PT) and strength training (ST) on the physical attributes of male adolescent team sports athletes, and further analyze the moderating variables that may have a potential impact on training effectiveness.